Pipe Inspection Robots for Structural Health and Condition Monitoring - Ogai, Harutoshi (Intelligent Systems, Control and Automation: Science and Engineering,, 2018)
This book highlights the state-of-the-art with regard to inline pipe investigation and structural health monitoring of pipes. The book begins with applications of pipe inspection robots, and goes on to discuss. robots that are developed for a mobile platform, various sensors employed to sense defects, and different data storage/communication systems employed for damage prognosis. The book also introduces smart materials and smart sensors for use in pipe inspection robots. The contents of this book will be useful to researchers and professionals alike. The structure of the book enables its use as a text in professional training and development coursework.